Balancing Business and Art in Music: Gazing into the Star Texts of Michelle Branch and Regina Spektor - (:unkn) unknown (My University, 2015)
This research builds on literature presenting ideas on the tension between business and art in the music industry and literature defining what a star is by analyzing star texts. Specifically, it looks at how business and art is balanced in the star texts of Michelle Branch and Regina Spektor and what tension this balancing creates. As the analysis follows the careers of these two case studies along their star texts, it reveals the tension created in relation to the record label, press, and fans of the music artists. The analysis discovers that music artists rely on social media to self-brand and create a star image similarly to how the public self-brands on social media. These findings make further research and analysis on the convergence of how celebrities self-brand and the consequences, and how the public self-brands and the potential consequences.
Keywords: Art and Business; Music Industry; Pop Music; Social Networks; Star Image; Star Text